Reconfigurable architecture based on fiber bragg gratings for indoor networks - Puerto-Leguizamón, Gustavo Adolfo; López-Sánchez, Wilson Ricardo; Suárez-Fajardo, Carlos Arturo (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2017)
This paper presents an approach for dynamic reconfiguration of wavelength channels for future indoor network architectures. The approach exploits the tunability and the rejection profile of Fiber Bragg Gratings (FBG) to implement service distribution strategies that includes Unicast, Broadcast and Multicast scenarios for fixed and mobile users. Experimental demonstrations based on two implementations show results with 1% average degradation for Error Vector Magnitude (EVM) values and up to 2,2 dB for 1x10-12 Bit Error Rate (BER). In particular, the proposed architectures fit for large in-building networks